Sensitivity index of HIV-1 model parameters with vertical transmission / Amiru Sule ... [et al.] - Sule, Amiru; Mamuda, Mamman; Mohammed Baba, Abdullahi; Lawal, Jibril; Usman, I.G (2015)
A non-linear deterministic mathematical model is considered to study the dynamics of HIV-1 with vertical transmission. The total population is divided into four mutually exclusive classes of susceptible, asymptomatic, symptomatic and AIDS individuals. Invariant region and positivity solution of the model is determined. The model threshold parameter is investigated using next generation operator method. Sensitivity analysis of the model parameters was carried out in order to identify the most sensitive parameters on the disease transmission.